2015
DOI: 10.1111/jrh.12129
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and Facilitators to Substance Use Treatment in the Rural South: A Qualitative Study

Abstract: This study identifies novel barriers and facilitators to substance use care in the rural South and highlights essential areas for consideration when developing and implementing substance use care in this geographic region. These findings can be used as guidelines to provide better care to individuals with substance use disorders living in rural communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
111
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(124 citation statements)
references
References 55 publications
11
111
0
Order By: Relevance
“…Single-entry point and co-located and/or integrated assessment, treatment, and case management services are key components of increasing treatment access among this vulnerable population (Drake et al, 2004; Minkoff, 2014). A recent qualitative study that examined barriers to client-centered treatment in rural communities found that flexible, community-based, wrap-around services that address substance use, mental health, and basic needs in an integrated way may increase the likelihood of individuals’ accessing treatment when significant barriers such as transportation, childcare, and geographic proximity to services in resource poor, rural communities are present (Browne et al, 2015). Integrated services must be flexible and client-centered to maximize treatment accessibility for individuals with COD, particularly those who face structural barriers to treatment (Kola & Krusynski, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Single-entry point and co-located and/or integrated assessment, treatment, and case management services are key components of increasing treatment access among this vulnerable population (Drake et al, 2004; Minkoff, 2014). A recent qualitative study that examined barriers to client-centered treatment in rural communities found that flexible, community-based, wrap-around services that address substance use, mental health, and basic needs in an integrated way may increase the likelihood of individuals’ accessing treatment when significant barriers such as transportation, childcare, and geographic proximity to services in resource poor, rural communities are present (Browne et al, 2015). Integrated services must be flexible and client-centered to maximize treatment accessibility for individuals with COD, particularly those who face structural barriers to treatment (Kola & Krusynski, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The results of several studies from the field of alcohol dependence, which are to some extent comparable, have identified facilitators different from those in our study. Browne et al (2016) pointed out as facilitators integrated services which meet clients' holistic needs such as housing, employment, help in obtaining appropriate clothing for job interviews, and flexible operating hours. These mainly relate to improving living conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also demonstrated that patients living in rural areas receive less follow‐up care after positive alcohol screening than patients living in urban areas . Additionally, a recent qualitative study found that while referral to specialty treatment is part of standard practice for patients with AUD among urban providers at the VA, rural providers viewed resources for AUD treatment to be unavailable and inadequate . It may be that PLWH in small rural areas receive less specialty addictions treatment because of these unique barriers to specialty care in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…High adherence rates have also been observed when HIV medications have been mailed directly to patients, and a similar model may increase access to AUD medications for PLWH who live in very rural areas and have an alcohol use disorder. Rural VA providers also cite lack of local collaborations as a reason for it being difficult to help patients access specialty care . Thus, increased partnerships with community‐based non‐VA care may help address under‐receipt of specialty addictions treatment for PLWH living in rural areas.…”
Section: Discussionmentioning
confidence: 99%